2013
DOI: 10.4275/kslis.2013.47.3.161
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Legal Deposit Guidelines for Online Digital Materials

Abstract: The purpose of this study is to suggest elements and guidelines for online digital materials in order to ensure its comprehensive collection, preservation, and access in Korea. For the establishment of elements and guidelines, this study examined appropriate advanced countries' legal deposit Acts, discussed with stakeholders, including experts and copyrighters in related areas, and surveyed library users' opinions. Finally, this study suggests 14 elements and guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…He then showed that there is no uniformity among countries world in this regard. Kwak et al (2013) also analyzed the guidelines for legal deposit of digital and online materials in the United Kingdom, New Zealand, Canada, France, Germany, and Finland, and presented an operational plan for depositing online and digital resources in Korea. So Stirling et al (2012) describes the legal situation in France regarding the legal deposit of digital material, and shows how it has been implemented in practice at the Bibliothèque Nationale de France (BnF).…”
Section: Introductionmentioning
confidence: 99%
“…He then showed that there is no uniformity among countries world in this regard. Kwak et al (2013) also analyzed the guidelines for legal deposit of digital and online materials in the United Kingdom, New Zealand, Canada, France, Germany, and Finland, and presented an operational plan for depositing online and digital resources in Korea. So Stirling et al (2012) describes the legal situation in France regarding the legal deposit of digital material, and shows how it has been implemented in practice at the Bibliothèque Nationale de France (BnF).…”
Section: Introductionmentioning
confidence: 99%